Cluster Management Technologies as the Tendency for Development of the Agricultural Industry - UKIBAYEVA, Gulim Kabikenovna; KOCHERBAYEVA, Ainura Anatolyevna; TEMIRBAEVA, Gulnara Rapikovna; DAUKENOVA, Gaukhar Amanzholovna; KURMANOVA, Dana Sultankhanovna (Journal of Environmental Management and Tourism, 2018)
The relevance of creating clusters is due to the fact that there is a need to switch to an innovative type of development. To increase the competitiveness of products and introduce innovations into production, the cluster is defined as a system of interrelated forms of various agricultural enterprises. In most countries, cluster development policy is an organizational form of industrial integration. Effective functioning of clusters leads to economic growth and increased competitiveness of the region economy. The main goal of the work is to consider the possibility of introducing a cluster and make a forecast of its effectiveness for the agriculture of the Kyrgyz Republic, on the basis of the chosen methodology. To achieve the objectives of the work, the following tasks were set and accomplished: review the theoretical aspects of the issue under research, conducting a SWOT analysis of the Chui oblast from the point of view of developing an agro-industrial cluster in it, calculate the clustering coefficients, choose a model for calculating cluster implementation efficiency, and propose a scheme for forming an agro-industrial cluster. The ability to create a cluster is calculated using the synergistic effect method. Methods of logical, statistical analysis were also used. The calculations show that the cumulative effect of factors leads to increased opportunities to create a cluster, and possibly in the future, will contribute to the effective development of the region and its international expansion. It is also confirmed that with the introduction of the cluster, the speed of agricultural development in the region will increase. The expected results of the cluster work can be different and depend on the interests of the participants: authorities, enterprises, etc. One of the main estimated results of cluster implementation is the improvement of the region's trade business, stable increase in the level of exports, and import substitution. The creation of a cluster, in our opinion, will contribute to the overall growth of the country's economy, improving food security and exporting competitive products.